2001
DOI: 10.1046/j.1523-1747.2001.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Excretion of Ultraviolet-Induced 8-Oxo-2′-deoxyguanosine and Thymine Dimers In Vivo: Implications for PUVA

Abstract: Molecular epidemiology has linked ultraviolet-induced DNA damage with mutagenesis and skin carcinogenesis. Ultraviolet radiation may damage DNA in one of two ways: either directly, leading to lesions such as cyclobutane thymine dimers (T<>T), or indirectly, via photosensitizers that generate free radical species that may ultimately produce such oxidative lesions as 8-oxo-2'-deoxyguanosine. We report the results of a pilot, case control study in which seven, healthy, human volunteers (skin type II; aged 23-56 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 54 publications
6
32
0
Order By: Relevance
“…The data for each day are expressed as a percentage of the total amount of T = T and compared statistically (t test) with day 3 (*, P < 0.05; **, P < 0.01; ***, P < 0.001). analyzed using an immunologic method (15,16). The results showed that T = T peaked at day 3 (15), which is consistent with our data.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The data for each day are expressed as a percentage of the total amount of T = T and compared statistically (t test) with day 3 (*, P < 0.05; **, P < 0.01; ***, P < 0.001). analyzed using an immunologic method (15,16). The results showed that T = T peaked at day 3 (15), which is consistent with our data.…”
Section: Discussionsupporting
confidence: 91%
“…analyzed using an immunologic method (15,16). The results showed that T = T peaked at day 3 (15), which is consistent with our data. However, the increase in T = T levels from the prestudy levels was much less in the reported study compared with ours.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The oxidized product of DNA, 8-hydroxy-2'-deoxyguanosine , is the most frequently measured biomarker of the oxidative stress [7,8]. The 8-OHdG has been analyzed in various kinds of samples, such as urine, serum, peripheral blood leukocyte, and organ tissue [9].…”
Section: Introductionmentioning
confidence: 99%
“…As the increase of oxidative stress may lead to oxidative DNA damage, we also measured the level of 8-hydroxy-2′-deoxyguanosine (8-OXO-dG), a marker of oxidative DNA damage, 17 in the liver of L-Atg5-KO mice. Indeed, as shown in Figure 2e, the 8-OXO-dG level was significantly higher in the liver of L-Atg5-KO mice than in the spleen of these mice or the liver of control mice at 2 and 4 months of age.…”
mentioning
confidence: 99%